Pengaruh Struktur Aktiva, Struktur Modal dan Karakteristik Perusahaan Terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel intervening Pada Perusahaan Perbankan Yang Terdaftari Di BEI Pada Periode 2020-2023 - Nouva Ayu Ramadhanti; Hwihanus (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the influence of asset structure, capital structure, and company characteristics on firm value with financial performance as an intervening variable in banking companies listed on the Indonesia Stock Exchange (IDX) during the period of 2020-2023. Using a descriptive quantitative approach and secondary data from annual reports, the research involves 10 banks selected randomly from a total of 47 listed banks. The analysis model employed is Partial Least Squares (PLS) with the assistance of SmartPLS software. The results indicate that both asset structure and capital structure have a significant impact on financial performance, with asset structure contributing more significantly than capital structure. Company characteristics do not show a significant effect on financial performance. Although financial performance does not directly influence firm value, it serves as an intervening variable that strengthens the effect of asset structure on firm value. These findings emphasize the importance of effective management of asset and capital structures to enhance financial performance and firm value, providing valuable insights for bank management in formulating better strategies in a competitive market.